THE PRACTICAL SIGNIFICANCE OF MODERNIST VIEWS ON THE ISSUE OF FAMILY CULTURE IN THE ISLAMIC RELIGION - M. R. Dehkonov (International Journal of Innovations in Engineering Research and Technology, 2021)
This article explains the culture of family relations in the Islamic religion, which for many centuries has played a positive role in the life of Muslims. The reason is that Islam has an enlightening effect on the family and its spiritual culture. Therefore in the culture of family relations, as well as religious values, national features, the spirit of the times and the achievements of science and technology are also manifested.In the process of creating a family in the context of modernization, a new type of parental relationship is formed, which affects the upbringing of children.